Manajemen Kurikulum Merdeka untuk PIAUD - Hecksa Manora; Nevi Laila Khasanah; Muhamad Akip (STAI Bumi Silampari, 2023)
This article discusses independent curriculum management in the context of early childhood Islamic education (PIAUD). The purpose of this research is to identify the concepts and principles of independent curriculum management and their implementation in PIAUD. The methodology used is a literature study with a descriptive-analytical approach. Based on the results of the research, the independent curriculum management concept emphasizes student empowerment as learning subjects and curriculum development that is tailored to the needs and potential of students. The principles of independent curriculum management include student participation in decision making, curriculum linkages with real life, flexibility in implementation, and competency development. The implementation of the independent curriculum in PIAUD requires a participatory curriculum development process that involves stakeholders, the use of active learning methods, and periodic evaluations to optimize the learning process. In conclusion, independent curriculum management can be an alternative for developing a student-centred PIAUD curriculum and developing their potential in a holistic and integrated manner.